Hospital Management using Gin Framework - Sona S; Thashmigaa E M; Menaha C. (International Journal of Engineering and Management Research, 2024)
The ever-evolving landscape of healthcare necessitates the development of efficient Hospital Management Systems (HMS) to optimize operational workflows and facilitate superior patient care. This paper introduces the design and implementation of an HMS using the Gin Framework, a lightweight and versatile web framework tailored for the Go programming language. The proposed HMS encompasses essential modules, such as patient registration, appointment scheduling, electronic health records (EHR), inventory management, and billing. Leveraging the Gin Framework's performance-oriented architecture, the system aims to streamline administrative processes, improve communication among healthcare professionals, and elevate the overall quality of healthcare services. The Gin Framework serves as the underpinning technology for the web application, offering a robust and scalable foundation. Through the utilization of RESTful API endpoints, the system ensures seamless integration with external services and devices, emphasizing interoperability and future scalability. Key functionalities of the HMS include user authentication, role-based access control, real-time updates, and a user-friendly interface. The implementation adheres to industry best practices, prioritizing security, data integrity, and compliance with healthcare standards. System evaluation involves comprehensive usability testing, performance analysis, and feedback solicitation from healthcare professionals and administrators. Results indicate that the HMS developed with the Gin Framework meets the requirements of a contemporary healthcare environment, delivering efficiency gains, improved data accuracy, and enhanced communication. In conclusion, this paper showcases the feasibility and efficacy of employing modern web frameworks, specifically the Gin Framework, to develop scalable and feature-rich healthcare management solutions. The proposed HMS contributes to ongoing efforts to enhance efficiency and quality in healthcare services, serving as a foundation for future advancements in hospital management technology.